Strategic Migration of Adobe Experience Manager : A Comprehensive Framework for On-Premise to Cloud Transition - Bhanu Phanindra Babu Gogula, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the strategic migration of Adobe Experience Manager (AEM) from on-premise environments to cloud platforms, addressing the growing demand for scalable and efficient content management solutions in the digital landscape. Through a comprehensive analysis of migration processes, this research presents a systematic framework for organizations undertaking AEM cloud transitions. The article investigates key components of migration, including code refactoring, configuration adjustments, content transfer strategies, and environment adaptation. Utilizing a mixed-method approach, incorporating both quantitative performance metrics and qualitative case study analysis, we evaluate the efficacy of migration tools such as Adobe's Cloud Acceleration Manager and custom scripts for business logic. Our findings reveal significant improvements in scalability, cost-efficiency, and system performance post-migration, while also highlighting potential challenges and mitigation strategies. This article contributes to the body of knowledge on enterprise content management systems and provides practical insights for organizations considering AEM cloud migration, offering a roadmap for successful transition in an increasingly cloud-centric technological ecosystem.
Keywords: AEM Cloud Migration; Digital Experience Platforms; Content Management Systems Cloud Computin; Enterprise Software Migration